Central nervous system toxins from conus textile venom - Corpuz, Gloria P.
Toxins from Conus textile venom which act on the central nervous system were partially purified. At least five toxins were resolved from gel filtration and ion-exchange chromatography. Both acidic and basic types of toxins were obtained. An active component which induced a distinct type of activity characterized by sudden running and convulsive seizures was partially purified and characterized. Symptomatology of this major type of activity is in many respects similar to that observed in conotoxin GIV. Unlike conotox in GIV, the C. textile toxin is relatively small (Mr<1400). The toxin may contain disulfide bonds which are reduced by dithiothreitol. Localization of CNS activity along the venom duct showed a concentration of the toxin components in the anterior duct region mainly associated with the soluble fractions. Venom proteins are predominatly acidic as shown by isoelectric focusing patterns. An LD50 of 36 mg/kg mouse on intracerebral injection was obtained.